A New Set of Measurements for the Materialism Scale - Trinh, Viet Dung; Phau, Ian (Australian and New Zealand Marketing Academy, 2012)
Materialism has always been a popular factor in marketing and consumer research. Until now, many researchers have still favoured Belk‟s materialism traits (1985) or Richins and Dawson‟ materialism scale (1992) in their works. However, previous literature suggested that the existing measurement did not capture the material distinctiveness of consumers (Atay and Sirgy, 2009; Mason, 2001). According to Mason (2001), materialistic consumers use their possessions to stand out of the crowd. Furthermore, recent failures of the existing materialism scales in explaining luxury brands related consumption have raised the question of whether it is time to review these measurements (Swami et al., 2009, Furnham and Valgeirsson, 2007). Working on the idea of materialism scale (Richins and Dawson, 1992) this paper presents a new 16-item scale developed to measure four components of materialism – namely material success, material happiness, material essentiality and material distinctiveness – and empirical evidence to support its validity.